Evaluation of serum autoantibodies against tumor-associated antigens as biomarkers in lung cancer. Issue 10 (October 2017) - Li, Pei; Shi, Jian-Xiang; Xing, Meng-Tao; Dai, Li-Ping; Li, Ji-Tian; Zhang, Jian-Ying
We evaluated autoantibodies against nine tumor-associated antigens, including p62, p16, Koc, p53, Cyclin B1, Cyclin E, Survivin, HCC1, and RalA as serological markers in lung cancer. Enzyme-linked immunosorbent assay (ELISA) was used to detect autoantibodies in sera from 50 lung cancer patients and 42 normal controls. Then, four tumor-associated antigens of higher values were selected and validated in sera from validation group. Western blot and serum absorption test were used to confirm positive findings from ELISA. When cutoff values were set as mean optical density values plus 3 standard deviation of normal controls, the positive rate of autoantibodies against four tumor-associated antigens (Survivin, Cyclin B1, HCC1, and p53) reached 32%, 20%, 22%, and 18%, with area under the curve values of 0.653, 0.767, 0.622, and 0.623 in sera from 50 lung cancer, respectively (all p < 0.05). Results from the validation group confirmed the results. When lung cancer patients were divided by their clinicopathological characteristics into different subgroups, we have found that serum anti-Cyclin B1 and anti-HCC1 autoantibodies increased in stages 1, 2, and 3 lung cancer; anti-Survivin autoantibodies increased in stages 2 and 3 lung cancer; and anti-p53 autoantibody only increased in stage 1 when compared with their corresponding levels in controls (all p < 0.05). Serum anti-Cyclin B1 and anti-Survivin autoantibodies increased with disease histological grade 2 and 3 (both p < 0.05). And higher serum level of anti-p53 autoantibodies is positively associated with tumor size. Parallel utilization of these four anti-tumor-associated antigens (any positive) can increase sensitivity to 65.0% at 100% specificity with area under the curve of 0.908 ( p < 0.001) in lung cancer detection in validation group. Our results suggest that autoantibodies against these four tumor-associated antigens have higher values in lung cancer detection, and serum anti-Cyclin-B1 has the potential to serve as novel non-invasive biomarkers in early-stage lung cancer.